The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1021/jm00172a023
|View full text |Cite
|
Sign up to set email alerts
|

7-Deaza-2-phenyladenines: structure-activity relationships of potent A1 selective adenosine receptor antagonists

Abstract: A series of derivatives of 7-deazapurines with varying substituents in the 2-, 6-, and 9-position was synthesized in an attempt to improve the adenosine receptor affinity and A1 or A2 selectivity. The adenosine receptor affinities were assessed by measuring the inhibition of [3H]-(R)-N6-(phenylisopropyl) adenosine (R-PIA) binding to rat brain A1 and inhibition of [3H]-5'-(N-ethylcarboxamido)adenosine (NECA) binding to rat striatum A2 adenosine receptors. A selected set of compounds representing the main struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…Sect. 4.1.2) [79]. The fusion of a six-membered ring at C(7) and C(8) of the deazapurine gives rise to this series.…”
Section: The 6 : 5 : 6-fused Tricyclic Heteroaromatic Systemsmentioning
confidence: 97%
See 4 more Smart Citations
“…Sect. 4.1.2) [79]. The fusion of a six-membered ring at C(7) and C(8) of the deazapurine gives rise to this series.…”
Section: The 6 : 5 : 6-fused Tricyclic Heteroaromatic Systemsmentioning
confidence: 97%
“…The most significant finding of this paper was the importance of the Ph group at C(7) of the ring. Further investigations of the 7-phenylpyrrolo[2,3-d]pyrimidin-4-amines revealed that a Ph group at C(2) was also beneficial (i.e., 29) [79]. Modifying the 7-Ph group to a chiral moiety showed that the (R)-enantiomer 30 was much preferred to the (S)-enantiomer 31 [79].…”
Section: The Adenosine a 1 Receptormentioning
confidence: 97%
See 3 more Smart Citations